The Inclusive Museum Leader - Catlin-Legutko, Cinnamon; Taylor, Chris (Rowman & Littlefield Publishers, 2021)
The museum field is experiencing a critical gaze that is both “of the moment” and long overdue. Museums were built as colonial enterprises and are slow to awaken to the harm caused by their actions which are not limited to the capturing and keeping of Indigenous ancestors, the exclusion and erasure of Black voices, bodies, and creativity, and the positioning of white power in the C-suite and board rooms. For decades, the conversation about equity and inclusion in the museum field has become louder. It is no longer possible to ignore the systemic racism embedded in our society and our profession. The Inclusive Museum Leader offers insights and perspectives from two recognized museums leaders who have joined together to offer practical solutions and opportunities for today’s museum leaders. Authors share their journeys to becoming inclusive leaders, as well as decisions they have made and actions they have taken to build equitable practices within their organizations. Throughout the book are personal exercises and provocations the reader is invited to respond to, making the book a valuable tool for any museum leader looking to enhance their style and re-frame their decision-making process.